Pengaruh Current Ratio, Debt To Equity Ratio, dan Asset Turn Over Terhadap Return On Invesment Perusahaan Manufaktur Indeks LQ45 Bursa Efek Indonesia - Mas'ula Mas'ula; Doni Teguh Wibowo (Fakultas Ekonomi dan Bisnis, Universitas Islam Raden Rahmat Malang, 2022)
The purpose of this research with the study of financial performance assessment is to examine the effect of the Current Ratio, Debt To Equity Ratio, Asset Turn Over on Return On Investment in manufacturing companies that are included in the LQ45 index. This research is a research in the field of financial management studies, especially regarding the measurement of the company's financial performance and financial performance analysis which is emphasized on the method of financial ratios. This type of research is quantitative research using ratio data. The population in this study are companies that are members of the LQ45 index of the Indonesia Stock Exchange. In this study, samples were taken using a porposive sampling method, namely companies that are members of the LQ45 index and are engaged in the manufacturing sector. The results of the current ratio measurement in research, the higher the current ratio value means the greater the company's ability to meet short-term obligations. The results of the calculation of the DER value, the smaller the value of the DER ratio, the greater the amount of capital owned by the company that can be used as debt security. The results of research on the value of TATO provide consideration for a company to increase sales or reduce some of its less productive assets. Meanwhile, the value of the profitability ratio is used to measure the company's ability to generate profits from its normal business activities. The results of the statistical test of the effect of the CR, DER, and TATO variables simultaneously on the ROI variable of 92.2%.